REFLECTIONS ON THE REFORM OF THE LEGAL SITUATION OF PEASANTS DURING THE KOŚCIUSZKO UPRISING OF 1794 - Konarski, Marcin (Review of European and Comparative Law, 2018)
The aim of this article is to analyse issues related to the reform of the legal status of the rural population during the Kościuszko Uprising, which was the first Polish national uprising. The analysis concerns the fundamental reform of the legal situation of peasants introduced by the uprising authorities in 1794, whose aim was to make this social group join the Uprising. The Commander-in-Chief – Tadeusz Kościuszko – announced the reduction of serfdom loathed by Polish peasants and lifted the ban on leaving the land without the permission of the owner. The defeat of the Uprising destroyed peasants’ hopes to be liberated from serfdom. However, it fostered their awareness of being members of the Polish Nation, contrary to the claims of the nobility and the magnates, who considered only their estate to be the Polish Nation and peasants to be their subjects, refusing them the attribute of being Polish.